Karakteristik Pembakaran Difusi Campuran Solar Murni dengan Minyak Kelapa - Jack C.A. Pah; Defmit B.N. Riwu; Adi Y. Tobe; Suprianto Siagian (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2020)
This research was conducted to determine the effect of adding coconut oil to pure diesel oil on the characteristics of diesel oil steam diffusion combustion. The characteristics observed are flame height and fire temperature. The combustion process is carried out on a circular tube burner. The steam mass flow of fuel in this study is 0.0895 grams / second. From the results of the study the biggest results were obtained in the mixture of 90% diesel oil with 10% coconut oil, fire height of 94.51 mm and a temperature of 967˚C and the lowest yield was found in a mixture of 70% diesel oil and 30% coconut oil, namely temperature amounting to 796˚C and fire height of 68.85 mm. From this, it can be concluded that the greater the percentage of diesel oil added to the combustion process, the higher and the flame temperature will increase. This is due to the characteristics of different fuels, where diesel oil has a lower viscosity than coconut oil and has a heating value greater than coconut oil.